2016
DOI: 10.1016/j.immuni.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Epithelial Reprogramming Underlies Mycobacterial Granuloma Formation and Promotes Infection

Abstract: SUMMARY Mycobacterium tuberculosis infection in humans triggers formation of granulomas, tightly organized immune cell aggregates that are the central structure of tuberculosis. Infected and uninfected macrophages interdigitate, assuming an altered, flattened appearance. Although pathologists have described these changes for over a century, the molecular and cellular programs underlying this transition are unclear. Here, using the zebrafish-Mycobacterium marinum model, we found that mycobacterial granuloma for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(199 citation statements)
references
References 48 publications
4
177
0
4
Order By: Relevance
“…Very recent work in our laboratories has confirmed these findings, demonstrating that only a subset of granulomas disseminate to form new, productive granulomas and showing that granuloma size at 4–5 weeks post infection correlates with dissemination 69 . Recent work in the zebrafish– Mycobacterium marinum model has identified similar crucial events in granuloma formation and organization that depend on the macrophage-specific reprogramming of adhesion pathways that are dependent on epithelial cadherin (E-cadherin; also known as cadherin 1) 70 . Disruption of this axis resulted in disordered granuloma formation and increased host clearance following increased neutrophil access.…”
Section: Granuloma Heterogeneitymentioning
confidence: 99%
“…Very recent work in our laboratories has confirmed these findings, demonstrating that only a subset of granulomas disseminate to form new, productive granulomas and showing that granuloma size at 4–5 weeks post infection correlates with dissemination 69 . Recent work in the zebrafish– Mycobacterium marinum model has identified similar crucial events in granuloma formation and organization that depend on the macrophage-specific reprogramming of adhesion pathways that are dependent on epithelial cadherin (E-cadherin; also known as cadherin 1) 70 . Disruption of this axis resulted in disordered granuloma formation and increased host clearance following increased neutrophil access.…”
Section: Granuloma Heterogeneitymentioning
confidence: 99%
“…55). Macrophages within the granuloma were reported to have an approximately sevenfold increase in ACE mRNA compared with kidney macrophages in a zebrafish model of Mycobacterium marinum infection, in which detailed cellular events that characterize granuloma formation can be visualized 56 . Fluorescence imaging and electron microscopy showed that forming granulomas undergo macrophage reprogram ming to express adherens-type cellular proteins, such as epithelial cadherin (E-cadherin; also known as CDH1), which are more typical of epithelial cells than myeloid cells, thereby allowing macrophages to form cell–cell contacts.…”
Section: Ace In the Immune Systemmentioning
confidence: 99%
“…The convergence of inflammation‐modifying hits onto the dopamine and CCK receptor signaling pathways was useful for the purpose of prioritizing compounds for further investigation. Expression profiling datasets (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE12189 and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE81913) demonstrate expression of dopamine and CCK receptors by zebrafish leukocytes and intestinal epithelial cells . Our infection experiments where cabergoline had an immunosuppressive effect in a model of systemic infection suggest a direct effect of dopamine receptor manipulation on zebrafish leukocytes.…”
Section: Discussionmentioning
confidence: 78%